Modifiable determinants of older adults' physical activity and sedentary behavior in community and healthcare settings: a DE-PASS systematic review and meta-analysis. - Ciaccioni, Simone; Compernolle, Sofie; Lerfald, Maren; Palumbo, Federico; Fadda, Floriana; Toma, Ginevra; Akpinar, Selcuk; Borodulin, Katja; Caglar, Emine; Cardon, Greet; Celen, Murat Cenk; Cieślińska-Świder, Joanna; et al. (European Review of Aging & Physical Activity, 2025)
Objectives: To identify the modifiable determinants targeted in interventions involving older adults, and to determine which of these interventions effectively increased physical activity (PA) and/or reduced sedentary behaviour (SB). Additionally, to explore whether the effects of these interventions vary based on the implementation setting. Methods: A search of randomized controlled trials (RCTs) and controlled trials (CTs) was performed in Medline, APA PsycArticles, SPORTDiscus, and Web of Science. Risk of bias assessment was performed with Cochrane's tool. Modifiable determinants were narratively synthesized, and random-effects models were performed to meta-analyse studies reporting device-measured physical activity or sedentary behaviour. Moderator analyses were performed to investigate the role of implementation setting. Standardized between-group mean difference (SMD) with 95% confidence interval (CI) was used to indicate effect sizes. Results: From 31,727 individual records, 52 eligible studies published between 2012–2022 were identified, 30 and 22 studies from community and health care settings, respectively. Determinants within the category physical health and wellbeing (n = 23) were most frequently reported while only one study reported determinants within a social or cultural context. Eighteen studies were included in the meta-analysis. Interventions targeting physical health and wellbeing revealed an increase in steps (SMD = 0.46; 95%CI: 0.15 to 0.77) and minutes of moderate-to-vigorous intensity physical activity (SMD = 0.41; 95%CI: 0.19 to 0.64) among intervention participants compared to controls, whereas interventions targeting psychological or behavioural determinants showed no between-group differences in steps (SMD = 0.10; 95%CI: -0.12 to 0.32) and moderate-to-vigorous intensity physical activity (SMD = 0.26; 95%CI: -0.24 to -0.75). Interventions targeting physical health and wellbeing showed significant heterogeneity (p < 0.0001; I = 73.10%). Subgroup analyses showed a significant effect on device-measured physical activity for the eight community-based interventions (SMD = 0.42; 95%CI: 0.07 to 0.77), while no significant effect was found for the eight studies performed in healthcare settings (SMD = 0.26; 95%CI; -0.10 to 0.62). Conclusion: Interventions targeting physical health and wellbeing may increase PA in older adults, with community-based studies appearing more effective than studies in healthcare settings. The significant heterogeneity of study findings indicates that further research is needed to fully understand the influence of PA and SB determinants across settings, particularly those related to psychological, behavioural, social, and cultural factors. Systematic review registration: PROSPERO: CRD42022287606.